Anaerobic co-digestion of alkali-pretreated submerged macrophytes and acidified food waste for reduction of neutralizing agents. (November 2017) - Koyama, Mitsuhiko; Nakahashi, Nobuo; Ishikawa, Kanako; Ban, Syuhei; Toda, Tatsuki
Abstract: Alkaline pretreatment for lignocellulosic biomass is beneficial for enhancing the anaerobic digestibility, but the rise of pretreatment cost and the dilution of substrate by the addition of a neutralizing agent and an alkaline solution are significant drawbacks. To solve these problems, utilization of acidified food waste as a co-substrate during anaerobic digestion of alkali-pretreated submerged macrophytes was attempted under various macrophyte to food waste (MF) ratio, and the biochemical interactions between the co-substrates were investigated. The addition of acidified food waste dropped the pH of alkali-pretreated Potamogeton maackianus, which reduced the dosage of neutralizing agent by 50% at MF 1:1. In co-digestion experiment, more CH4 was produced as the dosage of food waste increased. Volatile-solid-based and wet-weight-based CH4 yields for MF 1:1 were 37% and 118% higher than those for the alkali-pretreated macrophyte, respectively, because of the high degradability and organic matter content of the food waste. Comparison between the measured and theoretical COD balance of the co-digestion revealed that there is no positive synergistic effect in the CH4 recovery. Instead, the hydrolysis of the co-substrates is inhibited possibly due to the existence of dissolved lignin. Overall, the study demonstrates that anaerobic co-digestion of alkali-pretreated macrophytes and acidified food waste could be a feasible option for reducing the neutralizing agent cost and enhancing the volumetric CH4 yield. Highlights: Anaerobic co-digestion of alkali-pretreated macrophytes and acidified food waste. Reduction of neutralizing agent after pretreatment by the addition of food waste. Improvement of volatile-solid-based and wet-weight-based CH4 yield by co-digestion. Inhibition of hydrolysis of macrophyte and food waste possibly by dissolved lignin.